Enrichment of peat yields novel methanogens: approaches for obtaining uncultured organisms in the age of rapid sequencing. Issue 2 (14th January 2019) - Carson, Michael A; Bräuer, Suzanna; Basiliko, Nathan
ABSTRACT: Methanogens are among the oldest forms of life on Earth and are detectable in a wide range of environments, but our knowledge of their overall diversity and functioning is limited. Peatlands in particular host a broad range of methanogens that contribute large amounts of methane to the atmosphere, but are largely under-represented in pure cultures. Here, we anaerobically enriched peat with common growth substrates, supplements and antibiotics to identifying novel methanogen sequences and potential growth conditions. Over 3 years, we obtained 28 new mcrA sequences from taxa that have remained previously uncultured and undescribed beyond distantly related clones or sequences detected in environmental samples. Evidence suggests that the novel methanogens, representing five of the seven known orders, were capable of growing on H2 as well as acetate and at temperatures ranging from 6 to ca. 22°C. Methods involving the use of ampicillin proved useful, although obtaining high methane production in the absence of H2 was difficult. Our results also indicate that many methanogens may rely on bacterial symbionts (commonly Clostridium spp .). Such enrichment approaches represent a useful intermediary between maker-gene detection and isolation, allowing us to broaden our understanding of methanogen physiological ecology while potentially providing valuable sequence data. Abstract : In this study, we used classical culture-based methods paired with modern sequencing to highlight the potential benefits of enrichment-based approaches in identifying novel methanogens from northern peatlands.